Learning to make a difference: Christian Aid Ireland’s adaptive programme management in governance, gender, peace building and human rights - Booth, David; Balfe, Karol; Gallagher, Róisín; Kilcullen, Gráinne; O'Boyle, Sarah; Tiernan, Alix (ODI, 2018)
This paper assesses the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. Tackling the problems of poverty, vulnerability and exclusion that persist in parts of the world that continue to be affected by violence or political insecurity is difficult for several reasons. For one, because of the complexity of the prevailing social, economic and political systems, solutions to chronic problems are far from obvious. One response to this aspect of the challenge is adaptive programme design and management. This paper is the product of a multi-year collaboration between ODI and the core team of Christian Aid Ireland to assess the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. It explains the basis on which Christian Aid Ireland’s current five-year programme has become committed to an adaptive approach. It then describes and seeks to draw lessons from the programme’s first year of experience, considering the possible implications for implementation over the coming years. The authors find that to get full benefits from the move to adaptive management, the new ways of working and their underlying principles will need to become more embedded in organisational practices and cultures.

What is different about how INGOs do Adaptive Management/Doing Development Differently? - Green, Duncan (From Poverty to Power, 2019)